2017
DOI: 10.1038/nmat4936
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-wavelength-dependent small polaron trapping of photoexcited carriers in α-Fe2O3

Abstract: Small polaron formation is known to limit ground-state mobilities in metal oxide photocatalysts. However, the role of small polaron formation in the photoexcited state and how this affects the photoconversion efficiency has yet to be determined. Here, transient femtosecond extreme-ultraviolet measurements suggest that small polaron localization is responsible for the ultrafast trapping of photoexcited carriers in haematite (α-FeO). Small polaron formation is evidenced by a sub-100 fs splitting of the Fe 3p cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
337
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(371 citation statements)
references
References 51 publications
(110 reference statements)
21
337
4
Order By: Relevance
“…Time-zero and the instrument response function of 105 fs FWHM were determined using concurrent transient absorption of α-Fe 2 O 3 , which displays IRF-limited formation of a ligand-to-metal charge transfer state. 23,24 Transient spectra at a range of pumpprobe delay times are shown in Figure 4A, with kinetic slices at selected energies in shown in Figure 4B. These spectra are analyzed using both single-energy kinetic fits and a global fit using a sequential These time constants are taken from the global fit (τ=1/k), and are summarized with fit uncertainties in Table 1.…”
Section: Transient M-edge Xanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-zero and the instrument response function of 105 fs FWHM were determined using concurrent transient absorption of α-Fe 2 O 3 , which displays IRF-limited formation of a ligand-to-metal charge transfer state. 23,24 Transient spectra at a range of pumpprobe delay times are shown in Figure 4A, with kinetic slices at selected energies in shown in Figure 4B. These spectra are analyzed using both single-energy kinetic fits and a global fit using a sequential These time constants are taken from the global fit (τ=1/k), and are summarized with fit uncertainties in Table 1.…”
Section: Transient M-edge Xanesmentioning
confidence: 99%
“…18 This technique has been used recently to resolve ultrafast photophysics of heme model complex iron(III)tetraphenylporphyrin chloride 19 as well as carrier photophysics in metal oxide semiconductors such as α-Fe 2 O 3 , Co 3 O 4 , and NiO. [20][21][22][23][24]…”
Section: Introductionmentioning
confidence: 99%
“…To help resolve this dilemma, time‐dependent relaxation measurements are a promising way to elucidate the nature of the carriers and their lifetime. Hematite charge carrier dynamics have been studied extensively by transient absorption spectroscopy (TAS), 4D electron energy loss spectroscopy, and extreme ultra‐violet (XUV) spectroscopy . These different studies have shown relaxation dynamics in hematite spanning a wide range of timescales, with no consensus on the attribution of extracted time constants to specific processes such as charge carrier recombination, trapping, polaronic state formation, lattice expansion and cooling, or long lived holes on the surface …”
Section: Introductionmentioning
confidence: 99%
“…However, it has some critical drawbacks that should be overcome to obtain a high h STH , including a short hole diffusion length, poor conductivity, and a large overpotential for water oxidation. 2,3 A multitude of strategies have been developed to improve the PEC performance of hematite by addressing these shortcomings. Making a nanostructure (especially one-dimensional, small-diameter nanorods) can reduce the electron-hole recombination by shortening the actual diffusion distance of charge carriers.…”
Section: Introductionmentioning
confidence: 99%